The PHF: A comprehensive panel survey on household finances and wealth in Germany - Ulf von Kalckreuth; Martin Eisele; Julia Le Blanc; Tobias Schmidt; Junyi Zhu (Deutsche Bundesbank, 2012)
The Panel on Household Finances (PHF) is a new panel survey on household finances and wealth in Germany conducted by the Deutsche Bundesbank. It covers the balance sheets, pension claims, savings, incomes and work histories of households, together with some information on consumption patterns, attitudes, expectations and standard demographic characteristics. This paper introduces the survey, highlights its main methodological features and presents initial results. The first wave of the survey was carried out between September 2010 and July 2011. It encompasses a net sample of 3,565 randomly selected households in Germany. Wealthy households are oversampled using micro-geographic indicators. The survey is designed to be a full panel. The micro data will be made available for scientific use. The next wave is scheduled for 2014. Aside from being a self-contained and comprehensive survey on household finances in Germany, the PHF is part of the Household Finance and Consumption Survey (HFCS). This system of surveys collects ex ante harmonised micro data in every country of the euro area.
Keywords: C83; D10; D14; D31; 330; survey data; household panel; family economics; household finance; wealth distribution; portfolio choice